Effect of temperature on the crevice corrosion of nickel alloys containing chromium and molybdenum - Hornus, Edgar Cristian; Giordano, Claudia Marcela; Rodríguez, Martín Alejandro; Rebak, Raul Basilio (Electrochemical Society, 2015)
Fil: Hornus, Edgar Cristian. Universidad Nacional de San Martín. Instituto Sabato; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Unidad de Actividad de Materiales (CAC); Argentina